Drug Donations in Post-Emergency Situations - Autier, Philippe; Govindaraj, Ramesh; Gray, Robin; Lakshminarayanan, Rama; Nassery, Homira G.; Schmets, Gerard (World Bank, Washington, DC, 2013)
The objectives of this project were to conduct situation analyses on drug donations in East Timor (post-conflict country), El Salvador and Gujarat State in India (both affected by earthquakes), and Mozambique (floods), applying criteria derived from the Interagency Guidelines for Drug Donations; to determine how and whether the implementation of the Guidelines has affected the processes and outcomes of drug donations; and to build evidence to facilitate wider acceptance of the Guidelines. The study teams undertook to identify the organizations responsible for inappropriate donations, a step not often taken in earlier investigations. This information can now be used to facilitate educational initiatives aimed at preventing similar problems in the future. Awareness of the Guidelines was high and appropriate drug donations were made in El Salvador, Gujarat State in India and East Timor. In Mozambique, it was found that even with strong recipient awareness of the Guidelines and country ownership of the drug donation process, dumping and inappropriate donations occurred. International donors did not follow requests made by the Mozambique Government, and disruption of administrative systems by the floods affected capacity to ensure proper management of drug supplies. In the four countries, drug needs in the first few days following the emergency were often met through buffer stocks. A common feature noted in Gujarat, East Timor and El Salvador was that, in most instances, adequate drug supplies were provided during the acute phase of the disaster through the use of local buffer stocks, as well as by major donor agencies with expertise in providing immediate disaster aid of good quality. In the case of Gujarat, the presence of a large domestic pharmaceutical production capacity in India significantly aided the swift response following the occurrence of the earthquake. In Mozambique, warehouses that contained buffer stocks were flooded. The effectiveness of logistics software systems was closely dependent on local capacity and sustainability of the systems. The decision to use them for emergencies needs to be re-examined since the effectiveness of these tools is disputed. In India and Mozambique, elaborate manual record-keeping systems that the local staff were familiar with and experienced in maintaining, served as a better source of information than computer based systems that were not updated, lacked functioning equipment and required staff knowledgeable in the use of the program. In all four countries, no evidence was found to suggest that improvements are needed to the Guidelines. However, there is a continuing need for improved dissemination, mainly among specific donor groups such as bilateral organizations, diasporas and smaller organizations. Such targeting of information on drug donation practices would improve future outcomes.